دور الرشاقة الريادية في تحقيق التموضع الاستراتيجي: دراسة استطلاعية لآراء عينة من المديرين في شركات التجارة العامة في محافظة دهوك - العراق - الداؤد، ألفن ناظر ججو; ديرو، أرشد سعيد (جامعة الكوفة - كلية الإدارة والاقتصاد, 2023)
سعت الدراسة الحالية إلى تحديد طبيعة علاقة الارتباط والأثر بين الرشاقة الريادية والتموضع الاستراتيجي في عينة من شركات التجارة العامة في محافظة دهوك. أجريت هذه الدراسة بالاعتماد على المنطق الاستدلالي؛ ولتحقيق هدفها، تم صياغة ثلاثة فرضيات رئيسة مفادهما وجود علاقة ارتباط معنوية بين الرشاقة الريادية والتموضع الاستراتيجي؛ ووجود أثر معنوي لأبعاد الرشاقة الريادية في التموضع الاستراتيجي؛ ووجود فروقات معنوية لدى الشركات المبحوثة تجاه متغيرات الدراسة تبعا للسمات الشخصية للأفراد المبحوثين. لاختبار صحة الفرضيات، تم إعداد استمارة استبانة وزعت على عينة عشوائية تمثلت بالمديرين في شركات التجارة العامة في محافظة دهوك. تم الحصول على (167) استبانة صالحة للتحليل، والتي تم تحليلها من خلال مجموعة من الأساليب الإحصائية بالاعتماد على برنامج (V26 SPSS). توصلت الدراسة إلى مجموعة استنتاجات منها أن الرشاقة الريادية في الشركات المبحوثة تساهم ومن خلال أبعادها الثلاثة (الابتكار الجذري، والتدابير الوقائية، والاستباقية في تحقيق التموضع الاستراتيجي من خلال اعتماد أربع استراتيجيات وهي التمايز، وقيادة التكلفة، والجودة المدركة، وتنويع الأعمال. كما خلصت الدراسة إلى مجموعة من التوصيات، منها ضرورة قيام المديرين في الشركات المبحوثة بتعزيز أبعاد الرشاقة الريادية فيها، وان لا تكتفي بالحد الأدنى من الاستفادة، إنما الاستفادة القصوى مما تقدمه هذه الأبعاد لان ذلك لن يساعدها في فقط في تعزيز تموضعها الاستراتيجي، بل في عدة جوانب أخرى كالسلوك بريادية باستمرار، وخلق فرص جديدة وفريدة، وتحقيق أداء رياديا متميزا. This study aims to identify the correlation and effect between entrepreneurial agility and strategic positioning in a number of general trading companies in the Duhok Governorate – Iraq. Inductive reasoning was followed to conduct the present study, which depends on the questionnaire as the main technique to collect data. To achieve the research aim, three hypotheses were developed; the first indicates that there is a significant correlation between entrepreneurial agility dimensions and strategic positioning; the second indicates that entrepreneurial agility dimensions significantly impact on strategic positioning; the third indicates that there are significant differences among the companies considered towards the study variables according to the personal characteristics of the participants. Using a non-random sample technique, the questionnaire was distributed to managers in the companies under study; 167 questionnaires were valid for the analysis. The study used a group of statistical tools to analyze data by employing the (SPSS) package. The study reached a set of conclusions, including that the entrepreneurial agility in the considered companies contributes through three of its dimensions (proactiveness, preemptiveness, and radical innovation) to achieve strategic positioning by following four strategies, which are differentiation, cost leadership, perceived quality, and business diversification. In light of the results of the present study, the researchers suggest a number of recommendations, including that the managers in the considered companies need to enhance the dimensions of entrepreneurial agility in these companies, and not to be satisfied with the minimum benefit, but to make the maximum use of what these dimensions offer, because this will not only help them in enhancing their strategic positioning, but in several other aspects, such as constantly behaving in an entrepreneurial way, creating new and unique opportunities, and achieving outstanding entrepreneurial performance.
Keywords: استراتيجيات التمايز -- المزايا التنافسية -- الرشاقة التنظيمية -- اتخاذ القرارات -- العراق